2021
DOI: 10.3390/su13105738
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Natural Clay Mineral Adsorbent Filtration Systems in Wastewater Treatment for Potential Irrigation Purposes

Abstract: This project investigated the relative efficiencies of three pilot-scale constructed columns for enhancing drainage wastewater treatment processes to ensure compliance with Egyptian and international water quality criteria. In this investigation, basic materials (sand and gravel) and variable natural clay minerals zeolite (Z), diatomite (D) and bentonite (B) were utilized as packing materials to build up a Z column (ZC), D column (DC) and B column (BC), respectively. The three columns’ ability to remove pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…1 . The XRD pattern of natural bentonite revealed that the major mineral was montmorillonite, with quartz, kaolinite, and dolomite 8 , (Table 1 ). The patterns of Na-bentonite revealed that the major mineral is Na-montmorillonite; with minor amounts of kaolinite, and dolomite also present 31 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 . The XRD pattern of natural bentonite revealed that the major mineral was montmorillonite, with quartz, kaolinite, and dolomite 8 , (Table 1 ). The patterns of Na-bentonite revealed that the major mineral is Na-montmorillonite; with minor amounts of kaolinite, and dolomite also present 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Regeneration of the spent adsorbents (natural and Na-bentonite) was done by two chemical substances for comparison. The first substance was 1 M KCl 8 ; the two adsorbents were washed gently to remove ions from their surface, then with deionized water to remove any residual, then dried at 80 °C, and left to cool in a desiccator. For the second substance; the same previous method was applied to the spent materials, but with a neutral solution from 5 μM Ethylenedinitrilotetraacetic acid disodium salt dihydrate (Na2-EDTA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations